Tumor infiltrating lymphocytes as an endpoint in cancer vaccine trials - McCarthy, Patrick M.; Valdera, Franklin A.; Smolinsky, Todd R.; Adams, Alexandra M.; O’Shea, Anne E.; Thomas, Katryna K.; Van Decar, Spencer; Carpenter, Elizabeth L.; Tiwari, Ankur; Myers, John W.; Hale, Diane F.; Vreeland, Timothy J.; et al. (Frontiers in Immunology, 2023)
Checkpoint inhibitors have invigorated cancer immunotherapy research, including cancer vaccination. Classic early phase trial design and endpoints used in developing chemotherapy are not suited for evaluating all forms of cancer treatment. Peripheral T cell response dynamics have demonstrated inconsistency in assessing the efficacy of cancer vaccination. Tumor infiltrating lymphocytes (TILs), reflect the local tumor microenvironment and may prove a superior endpoint in cancer vaccination trials. Cancer vaccines may also promote success in combination immunotherapy treatment of weakly immunogenic tumors. This review explores the impact of TILs as an endpoint for cancer vaccination in multiple malignancies, summarizes the current literature regarding TILs analysis, and discusses the challenges of providing validity and a standardized implementation of this approach.